SOCIAL ISSUES RESEARCH REPORT THE EFFECT OF THE FREE NUTRITIOUS MEAL PROGRAM ON THE CONDITION OF THE POCKET MONEY OF STUDENTS OF SMA NEGERI 1 CIKARANG BARAT - Luhjingga Nadira Nadeswari (CV. KAMPUS AKADEMIK PUBLISHING, 2026)
The Free Nutritious Meal Program has been implemented in schools to improve students’ nutritional intake and support their learning activities. However, the program may also affect students’ financial conditions, particularly the use of their pocket money. This study aims to analyze the effect of the Free Nutritious Meal Program on students’ pocket money expenditure at SMAN 1 Cikarang Barat. A quantitative research method was employed using an interview approach. Data were collected through interviews with students and analyzed to identify changes in their spending patterns before and after the implementation of the program. The findings indicate that the availability of nutritious meals at school is associated with changes in students’ expenditures on food and beverages, allowing some students to save a larger portion of their pocket money or allocate it to other needs. However, responses to the program varied among students, as some continued to purchase additional food and snacks. These findings suggest that the program is related to changes in students’ spending patterns, although its influence differs among individuals. Therefore, further evaluation is needed to better understand its impact on students’ daily financial behavior.